Study of Aluminum Corrosion in Chloride and Nitrate Media and its Inhibition by Nitrite - Afzal, S. N.; Ali Shaikh, M. A.; Mustafa, C. M.; Nabi, M.; Ehsan, M. Q.; Khan, A. H. (Journal of Nepal Chemical Society, 2007)
Aluminum corrosion has been studied in aqueous chloride and nitrate media. Potentiodynamic method is applied to carry out the individual effect of chloride and nitrate ions on the commercial grade aluminum corrosion. In both chloride and nitrate media the corrosion behavior is affected at pH 4 and 10. The corrosion rate of aluminum increases with the increase of concentrations of chloride and nitrate ions. In both media corrosion behavior is significant at higher pH value due to the instant dissolution of metal ions as complex. The nitrite plays an important role as a corrosion inhibitor in both chloride and nitrate media. DOI: 10.3126/jncs.v22i0.519 Journal of Nepal Chemical SocietyVol. 22, 2007 pp.26-33